A indenização punitiva na tutela coletiva - Castro, Ana Paula de (2012)
The two main objectives of this study are: (i) advocate the application of punitive damages under the collective protection and (ii) submit, albeit briefly, some procedural implications of the application of punitive damages in class actions. To do this we started the work by mentioning the importance of protection of collective rights in a broad sense and presenting a panorama of several standards that deal with collective rights in a broad sense. In a second step, we analyze the evolution of liability and punitive damages as to present a new legal institution to be used for the prevention of collective damage. Finally, starting from the assumption that punitive damages can be used in the context of collective protection, some practical procedural aspects are mentioned in the application of punitive damages in class actions